E-Learning Culture In Mox - Gan, Chai Ling (2006)
This research is a study of the E-Learning Culture in Mox. The study was to evaluate how MOx employees experience E-Learning culture. Whether the E-Learning environment does support employees' development in their work and how we can motivate more employees to study.